CORRELATION OF PARITY WITH ABORTION IN RS ST ELISABET BATAM CITY - Omar Sazali Aldy; Ferry Daniel Martinus Sihombing (Universitas Batam, 2020)
Background : Abortion is the threat or release of the product of conception at â‰¤ 20 weeks of gestation. In the world there are 20 million cases of abortion every year and 70,000 women die from abortion each year. One of the causes of abortion, among others, parity, maternal age, infectious diseases. This study aims to determine the relationship between parity and abortion. Method : The research method used was an analytic survey with a cross sectional approach. Conducted at ST Elisabeth Hospital, Batam City, the study was conducted for 6 months, all pregnant women recorded in the medical records at Santa Elisabeth Hospital, Batam City, namely 242 pregnant women for the period 2020. Sampling was using total sampling technique with research instruments using checklists. Data analysis using Chi square. Result : The results showed that most pregnant women with primiparous parity were 126 people (52.1%). Of the 242 pregnant women, 124 (51.2%) did not abort and 118 (48.8%) experienced abortion. Based on the results of the chi-square statistical test analysis, the value of Ï value was 0.002 smaller than Î± (0.05). Conclusion : Which means that there is a significant relationship between parity and the incidence of abortion at Santa Elisabeth Hospital. Suggestions to further researchers to be able to expand the research by taking more samples from several other hospitals, in order to strengthen the accuracy of the research results.